Ligand-modified Biopolymeric Nanoparticles as Efficient Tools for Targeted Cancer Therapy - Kouchakzadeh, Hasan; Soudi, Tooba; Aghda, Niloofar H.; Shojaosadati, Seyed Abbas (Current Pharmaceutical Design, 2017)
Non-specific distribution of chemotherapeutic agents in the body where they affect both cancer as well as normal cells resulting in serious side effects is the major reason for the high mortality rate of cancer. Thus, there is a need for developing targeted delivery strategies specially employing nanoplatform-based cancer therapies that provide specific targeting to tumor cells. In this regard, biopolymeric nanoplatforms such as liposomes, protein- and polysaccharide- based nanoparticles have gained more attention due to their biocompatibility, biodegradability and less toxicity. In terms of targeting, monoclonal antibodies (mAbs), folic acid (FA) and transferrin (Tf) can be considered as the moieties to be attached to the nanoplatforms to deliver their payload to its site of action. This review article focuses on the recent progress in the field of targeted drug and gene delivery systems with emphasizes on liposomes, protein (specially human and bovine serum albumin)-based nanoparticles and polysaccharide (specially chitosan and dextran)-based nanoparticles as the biopolymeric nanoplatforms, which are decorated with mAbs, FA and Tf as the targeting ligands.
Keywords: cancer targeting